KESULITAN BELAJAR SISWA DALAM MATA PELAJARAN IPA TERPADU - Dinatha, Ngurah Mahendra (Universitas Nusantara PGRI Kediri, 2017)
Abstract:This study aims to determine the level of difficult study student in following the Natural Science Subject. This research is qualitative descriptive. The sampling technique used is simple random sampling. Research conducted in Junior High School of Widiatmika, Badung Regency, Bali. The number of the sample members are 30 people. Data collected to measure the level of student difficult in Natural Science Subject, the questionanire method was used. Data were analyzed descriptively with references to the theoretical scale. The results of this study concluded that difficult study in Natural Scinece Subject said to be in the category of